OPTIMALISASI SEL Saccharomyces cerevisiae UNTUK MENINGKATKAN PRODUKTIVITAS DAN EFISIENSI INDUSTRI ETANOL [Optimization of Saccharomyces cerevisiae Cell to Increase Productivity and Efficiency of Ethanol Industry] - Rustiaty, Banon (Jurnal Teknologi & Industri Hasil Pertanian, 2018)
The development of bioethanol as fuel substitution is believed to overcome the potency of the world energy crisis including Indonesia. The bioethanol development can be done by increasing the production capacity of the existing bioethanol factory plant by improving yeast culture for enhancing the performance of the fermentation process. This study was aimed at obtaining a method of optimizing the ability of Saccharomyces cerevisiae fermentation that can be applied by the alcohol industry in Indonesia for increasing factory productivity, thereby reducing the cost of producing alcohol. In this study, the adaptation of Saccharomyces cerevisiae Watei and Saccharomyces cerevisiae Hakken I were adopted in environment condition with high ethanol content up to 13%. The results showed that the yeast was able to grow in environments with high ethanol content with higher specific growth rate and larger cell size than those within the original yeast. This condition showed that adapted strains can overcome stress caused by high ethanol. These results promise the good performance yeasts with ability in growing and performing metabolic activities in high alcohol-containing environment conditions